2021
DOI: 10.3389/fnut.2021.721733
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review on Phytochemical Profile and Biological Effects of Turnip (Brassica rapa L.)

Abstract: A growing number of medicinal and edible plants have attracted increasing attention due to their abundant constituents and biological activities including turnip. Turnip (Brassica rapa L.) is an herbaceous biennial plant belonging to Cruciferae Brassica. As one of the oldest cultivated vegetables widely consumed in Asia, the turnip has received significant attention in the studies of its bioactive components and biological function. Multiple bioactive components in turnip, such as glucosinolates, isothiocyanat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…They can be divided into four major classes: terpenoids, and sulfur-containing compounds such as glucosinolates (GSLs), alkaloids, and phenolics [7,8]. Over recent decades, plant secondary metabolites such as GSLs have been gaining great interest because of their cancerpreventive properties for humans as well as their nutritional value [2,[9][10][11], which evoked the demand for the breeding of functional cultivars and industrial applications [12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They can be divided into four major classes: terpenoids, and sulfur-containing compounds such as glucosinolates (GSLs), alkaloids, and phenolics [7,8]. Over recent decades, plant secondary metabolites such as GSLs have been gaining great interest because of their cancerpreventive properties for humans as well as their nutritional value [2,[9][10][11], which evoked the demand for the breeding of functional cultivars and industrial applications [12].…”
Section: Introductionmentioning
confidence: 99%
“…Human intake of these vegetables rich in the ITCs is known to help reduce the risk of cancer [18,19]. In addition, it is well-known that GSLs play a crucial role in the defense and survival system of the Brassicaceae [11,20], and it has been reported that GSLs might act as a sink for nutrients, such as nitrogen and sulfur [21][22][23]. Nonetheless, the physiological significance and mechanistic regulations of GSLs and their degradation products in many plants are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glucosinolates and their breakdown products have been reported to reduce the risk of lung, colon, and other types of cancer ( Mandrich and Caputo, 2020 ). Phenolic compounds in plants possess potential health-promoting effects, including antioxidant, anti-inflammatory, anti-microbial, anti-obesity, and anti-tumour activities ( Cao et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides in natural extracts are generally non-cytotoxic and have a variety of biological activities; they can activate immune cells and promote the secretion of cytokines, thereby regulating the immune system (Shinchi et The polysaccharide content in the water extract of turnips from Aksu Keping County, which had the best quality in Xinjiang, was as high as 11.53%. The water extract of turnip also had strong ability to scavenge free radicals (Cao et al 2021). Two homogeneous polysaccharides, namely, two Brassica rapa L. neutral polysaccharide (BRNP) and two Brassica rapa L. acid polysaccharides (BRAP), were isolated from the crude polysaccharides of turnip for the rst time by chromatography and spectroscopic techniques (Qiao et al 2020;Li et al 2021;Hairenguli et al 2020).…”
Section: Introductionmentioning
confidence: 99%